PERBANDINGAN HASIL PENGUKURAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI BERBAGAI POSISI TUBUH - Renita Anankaristi; Dwi Ari Murti Widigdo; Bambang Sarwono; Sunarmi Sunarmi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2026)
Blood pressure is influenced by various factors, including age, sex, and body position during measurement. Variations in body position, particularly the lateral position, may affect hemodynamic status and potentially result in differences in blood pressure values. This quantitative study employed a comparative design to determine differences in systolic blood pressure (SBP), diastolic blood pressure (DBP), and Mean Arterial Pressure (MAP) among hypertensive patients measured in the supine, left lateral, and right lateral positions. The study involved 65 respondents selected using non-probability sampling with a purposive sampling technique. The inclusion criteria were male and female patients aged 40–60 years, having both upper limbs intact, and not being ill or experiencing paralysis. The instruments used included a digital sphygmomanometer, a standard operating procedure (SOP) for blood pressure measurement, and an observation sheet. Data were analyzed using the Kruskal–Wallis test and epsilon squared (ɛ²) effect size calculation. The Kruskal–Wallis test showed statistically significant differences in SBP, DBP, and MAP among the three measurement positions (p = 0.000 [<0.001]). The highest mean values of SBP, DBP, and MAP were found in the supine position, while the lowest were observed in the right lateral position. The effect size (ɛ²) was categorized as relatively strong (0.16–0.36). Body position was shown to have a relatively strong influence on blood pressure values in hypertensive patients. These findings highlight the importance of maintaining consistent body positioning during blood pressure measurement to ensure accurate and comparable results.